2008
DOI: 10.1177/147323000803600219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Isolated Systolic Hypertension in the Rural Adult Population of Liaoning Province, China

Abstract: The prevalence of and associated risk factors for isolated systolic hypertension, as defined by the Joint National Committee (JNC)-6 classification, were investigated in the rural population of Liaoning Province, China. A total of 45,925 people aged 35 years or older were examined in a cross-sectional study. Overall, the prevalence of isolated systolic hypertension was 10.6% (males 10.1%; females 11.2%). The prevalence of isolated systolic hypertension was positively correlated with age, gender, smoking status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
9
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 11 publications
11
9
2
1
Order By: Relevance
“…A similar finding was supported by Xu et al in China. [5] In our study, prevalence of ISH was equally distributed (13.6%) among subjects who had <5 and >5 servings of green leafy vegetables/day (25%), and this observation was supported by the similar study done by Jagdal et al (47.2%) in Mongolia. [4] In our study, prevalence of ISH (26.5%) was found high among the individuals who had <5 servings of fruits/day.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…A similar finding was supported by Xu et al in China. [5] In our study, prevalence of ISH was equally distributed (13.6%) among subjects who had <5 and >5 servings of green leafy vegetables/day (25%), and this observation was supported by the similar study done by Jagdal et al (47.2%) in Mongolia. [4] In our study, prevalence of ISH (26.5%) was found high among the individuals who had <5 servings of fruits/day.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, the highest (27%) prevalence of ISH was observed in 70-79 years of age group. The prevalence of ISH was found to rise with increase in age, and this was comparable and found almost similar with the study done by Mandal et [3,5] Epidemiologic transition and increase in life expectancy accompanying the demographic change had been associated with an increase in a number of the elderly and the burden of NCDs like hypertension and its subtypes. The present study also adds to this evidence.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…19 Hasil penelitian ini sejalan dengan penelitian berikutnya yang menyatakan bahwa lansia yang merokok mempunyai kemungkinan sebesar 1,179 kali dan 1,07 kali, lebih besar terkena hipertensi hipertensi sistolik dibandingkan dengan lansia yang tidak merokok. 20,21 Berdasarkan hasil penelitian ini didapatkan bahwa tipe-tipe perilaku merokok yang paling banyak adalah karena zat adiktif dan kebiasan yaitu sebesar 60%. Mereka menggunakan rokok sama sekali bukan karena untuk mengendalikan perasaan mereka, tetapi karena benar-benar sudah menjadi kebiasaan rutin.…”
Section: Perilaku Merokok Respondenunclassified